2003
DOI: 10.1046/j.1322-7114.2003.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Job stress, coping and health perceptions of Hong Kong primary care nurses

Abstract: Few empirical studies have investigated job stress, coping and health perceptions of nurses working in primary care settings. One thousand self-report questionnaires, which consisted of the modified Nursing Stress Scale, Coping with Work Stress Checklist and Health Perceptions Questionnaire, were distributed randomly to a group of Hong Kong nurses working in primary care settings, to examine issues related to job stress. Three hundred and sixty-two nurses responded. Findings indicated that nurses in these sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 32 publications
1
39
1
8
Order By: Relevance
“…Furthermore, Lee (2003) used a self-report questionnaire in his study and mentions recreation and meditation as coping strategies employed by nurses. Also, he states that being unable to cope with stress endangers the health of nurses and that avoidance strategies are the most common ones used by nurses 4) . Dominguez-Gomez and Rutledge (2009) point out that getting away from patients is an avoidance strategy employed by nurses 23) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Lee (2003) used a self-report questionnaire in his study and mentions recreation and meditation as coping strategies employed by nurses. Also, he states that being unable to cope with stress endangers the health of nurses and that avoidance strategies are the most common ones used by nurses 4) . Dominguez-Gomez and Rutledge (2009) point out that getting away from patients is an avoidance strategy employed by nurses 23) .…”
Section: Discussionmentioning
confidence: 99%
“…McGrath et al (2003) consider colleagues' support as a factor for decreasing stress 9) . Other studies found that the following strategies can decrease the amount of stress experienced by nurses: giving value to nurses' opinions, and respecting their profession 27) , talking to intimate friends, interpersonal and organizational communication 25) , colleague's support, appropriate training, and attending conferences to get upto-date information 29) , maintaining social interaction, getting help from the colleagues 4) , having a sense of importance due to the support of superiors and colleagues 1) , creating an appropriate working situation by nurse managers 30) , and effective interaction among nurses 31) . The core category in this study was "On the route to coping" used to explain the overall phenomenon of nurses coping with job stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practically, they attend meetings, take minutes, supervise, monitor, research, publish, engage in extension services and ensure that deadlines are met. The University administrator is therefore more vulnerable and susceptible to stress than lecturers (Lee, 2003). The female university administrator, specifically, is more challenged in dealing with stress since she would have to manage her home first by making sure that the home is given a conducive environment for the sustenance of her family is more liable stress than their male counterparts.…”
Section: Quality Education International Journal Of Academic Researchmentioning
confidence: 97%
“…[4] The occupational stressors nurses encounter can differ between countries, [5] between urban and rural areas, [6] and between hospitals and primary health care. [7] The major sources of stress for nurses employed in primary health care settings were identified as their workload, conflicts with physicians, and conflicts with other nurses. To a lesser extent, inadequate preparation, lack of support, encountering death and dying, and uncertainty concerning treatment were also reported.…”
Section: Introductionmentioning
confidence: 99%